Automated writing evaluation tools for Indonesian undergraduate English as a foreign language students’ writing - Delsa Miranty; Utami Widiati; Bambang Yudi Cahyono; Tengku Intan Suzila Sharif (Institute of Advanced Engineering and Science, 2023)
Nowadays, many computer programs are used in the teaching of writing in the context of English as a foreign language (EFL). One of the functions of the computer programs is to provide feedback to EFL students’ writing so that the quality of their writing can be improved. This study aimed to investigate whether the use of free automated writing evaluation (AWE) tools affect undergraduate EFL students’ writing skills. In this experimental study, 35 Indonesian undergraduate students of English education department were asked to use two AWE tools, Grammarly and Grammark, in the writing course over four months. Data for this study were collected by using tests and questionnaire. Pre-test, middle test, and post-test were administered to examine the students’ writing skill improvement. The findings indicate that the sequenced use of two AWE tools, Grammarly followed by Grammark, had a beneficial effect on students’ writing skill improvement. This study confirms the benefits of free AWE tools in enhancing EFL students’ writing skills.